2012
DOI: 10.1039/c1pp05133d
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 MAP kinase and JNK pathways by UVA irradiation

Abstract: There are more than two million new cases of non-melanoma skin cancers (NMSCs) diagnosed each year in the United States. The clear etiological factor is chronic exposure to solar radiation from the sun. The wavelengths of solar light that reach the earth’s surface include UVB (280-320nm) which accounts for 1-10% and UVA (320-400nm) which accounts for 90-99% of the radiation. While most of the published research has focused on the effects of UVB, little is known concerning UVA-mediated signal transduction pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 100 publications
(231 reference statements)
2
34
0
1
Order By: Relevance
“…Among the lipid photoproducts that we and others detected here but also earlier are mediators that promote pro-inflammatory signaling: Oxidized PAPC can induce p38 MAPK signaling that in turn leads to expression of COX-2 [40] and p38 MAPK is essential for COX-2 expression in response to UV [55]. Platelet activating factor (PAF) -like lipids that were identified as important signaling photoproducts can promote TNF alpha synthesis upon UV exposure [56].…”
Section: Signaling Pathways Utilized By Lipid Photoproductsmentioning
confidence: 85%
“…Among the lipid photoproducts that we and others detected here but also earlier are mediators that promote pro-inflammatory signaling: Oxidized PAPC can induce p38 MAPK signaling that in turn leads to expression of COX-2 [40] and p38 MAPK is essential for COX-2 expression in response to UV [55]. Platelet activating factor (PAF) -like lipids that were identified as important signaling photoproducts can promote TNF alpha synthesis upon UV exposure [56].…”
Section: Signaling Pathways Utilized By Lipid Photoproductsmentioning
confidence: 85%
“…Correspondingly, migration of human CEC was dramatically enhanced following treatment with either IL-1β or FGF2, and this could be completely abolished by co-treatment with SU5402, a pan FGF antagonist, or IL-1Ra (Figure 1C). Because p38 works as an upstream regulator for AP-1 (Lin et al, 2009; Kook et al, 2011; Zhang and Bowden, 2012) and because activation of NF-κB is mediated by IKK phosphorylation (Kim et al, 2006; Hayden and Ghosh, 2008) in various cell types, we used ELISA to investigate whether IL-1β stimulation results in AP-1 and NF-κB activation in human CEC. Both AP-1 and NF-κB activities were greatly induced by IL-1β, and co-treatment with IL-1Ra nearly extinguished the IL-1β dependent activation of AP-1 and NF-κB in human CEC (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiological effect of UVR-induced activation of both p38 and JNK in keratinocytes is controversial, as reports show that these stress response proteins can elicit both pro- and anti-survival mechanisms [104]. However, given the bimodal role that oxidative stress plays in cancer, this seemingly contradictory response is not surprising.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Other reports indicate that UVR-induced p38 activation induces NOXA-dependent apoptosis through increased protein expression of hypoxia-inducible factor 1-alpha (HIF-1α) in a p53-independent manner [114]. In contrast, it has been shown that p38 activation increases UVR-induced survival of keratinocytes though upregulation of the cancer associated genes Bcl-XL and COX-2 [104]. Activation of p38 can also directly phosphorylate glycogen synthase kinase 3 beta (GSK3β) at Thr 43 and Thr 390 (Ser 389 in mice), which promotes β-catenin dependent growth and proliferation [115].…”
Section: Oxidative Stressmentioning
confidence: 99%